KONTRIBUSI IBU RUMAH TANGGA TERHADAP PENDAPATAN KELUARGA (Studi Kasus: Pengrajin Kerawang Di Desa Mongolato Kecamatan Telaga Kabupaten Gorontalo) - Sri Belawati Talipi; Benu Olfie L. S; Vicky R. B. Moniaga (AGRI-SOSIOEKONOMI, 2018)
This study aims to identify what percentage contribution of housewives to family income, income Husband, and income Children. The research was conducted by Mongolato Village of Telaga District of Gorontalo.The research method was Purposive Sampling method, ie 40 (forty) respondents, Number of housewives working in kerawang workshop business group in Mogolato Village, Telaga District. Data collected in this research is data primary and secondary data with the method of data analysis using descriptive analysis. The results of research in Mongolato Village indicate that the contribution of housewife embankment income Kerawang to household income is sebersar 39.92% of the total income of the whole family. And if seen from Age Household Contribution Most housewives are at productive age 36 until 40 Year that is equal to 66,40%, whereas if seen from education level Household contribution is mostly found at level of elementary education that is 42,79%, because level of education does not affect the creativity of the Housewife. And if seen from the number of dependents The contribution of the most housewives is in â‰¤ 1 which is 40%, because housewife who have children â‰¤ 1 more spare time to do Sulam Krawang than housewife who has more dependents / children.